Assessment of the ecological efficiency of the open development of non-metallic deposits of useful minerals - Simonenko, Vladimir; Pavlychenko, Artem; Cherniaiev, Oleksii (Technology audit and production reserves, 2018)
The object of research is the environmental safety of the functioning of mining enterprises. One of the most problematic places there are significant differences in the mining and geological conditions and geometrical parameters of the quarries, the type and technical condition of the mining and transportation equipment used in mining enterprises, as well as the need to refine reserves in a reduced sanitary protection zone. Changes in the procedure for assessing the environmental impact of a planned activity by mining enterprises should include the development and implementation of additional technological solutions that will help reduce pollution in the adjacent territories. Therefore, there is a need to develop standardized approaches, the use of which will allow analyzing the technological processes of mining enterprises and be more dangerous from an environmental point of view, where significant amounts of pollutant emissions are generated. In the course of the study, three typical technological schemes for the development of deposits of rocky building materials, differing in productivity and emissions of pollutants to adjacent territories, have been analyzed. It has been established that the use of belt conveyors allows reducing the zone of influence of an enterprise on the ecological state of adjacent territories and minimizing the environmental risks of the functioning of mining enterprises. For the localization of emissions of pollutants in the mining enterprise, it is reasonable to place mobile and portative crushing and screening plants in a quarry directly in the faces or at work sites. This will reduce environmental pollution levels and increase the comfort of living in the mining regions. Thanks to the use of modern research methods, methods of cartographic modeling and scientific forecasting and the use of computer programs, optimal environmental-friendly field development technologies have been developed. Their use will reduce emissions of pollutants outside the sanitary protection zone and improve the environmental image of the mining enterprise. Such approaches will contribute to the successful passage of the environmental audit of mining enterprises, obtaining international environmental certificates and the development of new markets for products.